Effects of water deficit and different nitrogen fertilizer treatments on the quality of wheat for Chinese fresh white noodles and steamed bread and the composition of storage proteins. (9th August 2019) - Li, Mengfei; Deng, Xiong; Xu, Xuexin; Liu, Nannan; Wang, Zhimin; Yan, Yueming
Abstract: BACKGROUND: Noodles and steamed bread are popular wheat products consumed worldwide, particularly in China and other Asian countries. We performed the first comprehensive study of the influence of water deficits and different nitrogen fertilizer applications on two elite Chinese bread wheat cultivars, Zhongmai 175 and Jimai 22, which are distinct in gluten strength. These wheat cultivars were tested to determine the qualities that are optimal for the production of Chinese fresh white noodles (CFWN) and northern‐style Chinese steamed bread (NCSB), and storage protein composition. RESULTS: Water deficit and high nitrogen (N) fertilizer application promoted total grain protein content and the accumulation of gliadins and glutenins, while low N resulted in the opposite results. Water deficit and high N fertilizer in Jimai 22, with medium‐to‐strong gluten strength significantly improved NCSB and CFWN qualities. The quality of CFWN under low N, and that of NCSB under both high and low N conditions, was significantly reduced. However, NCSB and CFWN quality in Zhongmai 175 with weak‐to‐medium gluten strength was not significantly affected by water deficit and different N fertilizer applications. Grain subproteome analysis revealed that considerable cultivar‐specific gliadins and glutenins showed significant accumulation changes in response to water deficit and high / low N fertilizer treatment, which could be responsible for NCSB and CFWN quality changes under different treatments. CONCLUSION: Water deficit and high / low N fertilizer treatments caused changes in cultivar‐specific storage protein composition, resulting in differences in the accumulation of gliadins, glutenins, and the quality of NCSB and CFWN. © 2019 Society of Chemical Industry